The Effect of Audit Tenure, Audit Fee, Audit Firm Size, and Auditor Specialization on Audit Quality in Non-Bank Financial Industry Companies (2017-2019) - Hardiyanti, Siti (Jurnal Cakrawala Akuntansi, 2024)
The purpose of this study is to examine how audit tenure, audit fee, auditor specialization, and the size of public accounting firms (KAP) affect the quality of audits in non-bank financial corporations that are listed on the Indonesia Stock Exchange between 2017 and 2019. Purposive sampling was the sample technique employed, and over the course of three years, 69 observations from 23 companies were obtained. With audit quality as the dependent variable, logistic regression was used to analyze the data. The study's findings show that audit fees significantly impact audit quality, but audit tenure, PCA size, and auditor specialization have no discernible effects. The premise that increased audit fees allow auditors to conduct more thorough and superior audit procedures is supported by these data. When it comes to evaluating the elements that affect audit quality, this study has significant ramifications for businesses and investors. Therefore, choosing qualified and impartial auditors is essential to enhancing the validity of financial reports.